2020
DOI: 10.1007/s11432-020-2806-8
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based vertical thin film transistors

Abstract: Vertical field effect transistors (VFETs), where the channel material is sandwiched between source-drain electrodes and the channel length is simply determined by its body thickness, have attracted considerable interest for high performance electronics owning to their intrinsic short channel length. To enable the effective gate modulation and current switching behavior, the electrode of conventional VFET is largely based on perforated metals, in which the gate electrical field could penetrate through. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…The active channel materials (MoS2, WSe2) can be pre-fabricated and transferred layer-by-layer within temperature < 200 °C, compatible with various back-endof-line (BEOL) process. Furthermore, the vertical stacking of different 2D materials can also be realized using graphene as the contact electrode [62][63][64]. For example, a complementary vertical inverter was created by vertically stacking the layered 2D MoS2 (n-type), 2D graphene (metallic) and 2D Bi2Sr2Co2O8 (p-type), as shown in Figs.…”
Section: Different 2d Channel Materialsmentioning
confidence: 99%
“…The active channel materials (MoS2, WSe2) can be pre-fabricated and transferred layer-by-layer within temperature < 200 °C, compatible with various back-endof-line (BEOL) process. Furthermore, the vertical stacking of different 2D materials can also be realized using graphene as the contact electrode [62][63][64]. For example, a complementary vertical inverter was created by vertically stacking the layered 2D MoS2 (n-type), 2D graphene (metallic) and 2D Bi2Sr2Co2O8 (p-type), as shown in Figs.…”
Section: Different 2d Channel Materialsmentioning
confidence: 99%
“…There is also enduring interest in the technological applications of two-dimensional (2D) materials, including graphene, for display devices [28], flexible sensors [29][30][31], photo detectors [32][33][34][35][36], vertical field-effect transistors [37,38], and atom chips [27]. New properties and methods of cooling or patterning 2D materials have been studied [39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Black phosphorus (b-P) was synthesized by phase transition of white phosphorus under high pressure in 1914 [1], and it was reported that the bulk b-P was a kind of semiconductor in 1986, but its quality was too difficult to control and it hardly attracted people's interest [2]. Mechanical exfoliation and transfer technology has developed rapidly since graphene was discovered [3][4][5][6], and two-dimensional (2D) b-P has received widespread attention [7]. In 2014, several groups revealed the properties of monolayer or few-layer b-P through theoretical calculations and experiments, which shows outstanding properties, such as tunable bandgap [8], in-plane anisotropy [9] and high carrier mobility [10].…”
Section: Introductionmentioning
confidence: 99%